Nicoletella semolina in the airways of healthy horses and horses with severe asthma. (4th May 2021) - Payette, Flavie; Charlebois, Audrey; Fairbrother, Julie‐Hélène; Beauchamp, Guy; Leclere, Mathilde
Abstract: Background: Nicoletella semolina was identified in the airways of horses and its low prevalence could be because of its difficult differentiation from other Pasteurellaceae . Objectives: To develop a molecular method for the identification of N. semolina and to evaluate its prevalence in the mouth and the airways of healthy and severe asthmatic horses. Animals: Six healthy and 6 severely asthmatic horses in phase I, 10 severely asthmatic horses in phase II, and 10 healthy horses in phase III. Methods: Cohort (phases I and II) and cross‐sectional (phase III) studies. Quantitative polymerase chain reaction primers targeting the sodA gene were optimized. N. semolina was quantified in oral and nasal washes and in bronchoalveolar lavage fluid (BALF; phase I, sampled twice), in nasal washes and BALF (phase II, sampled twice), and in nasal washes (phase III). Results: N. semolina was found in the nose of 5, 10, and 9 horses in phases I, II, and III, respectively (first sampling for phases I and II). Six BALF from 5 different horses were positive for N. semolina in phase II. In phase I, there was no significant difference in the nasal loads of healthy horses (median (range): 2.04 × 10 4 copies/mL (0‐2.44 × 10 5 )) and asthmatic horses in exacerbation (3.75 × 10 2 (0‐4.84 × 10 6 ); Wilcoxon's rank sum test, P = .57). Conclusions and Clinical Importance: N. semolina is commonly found in the airways of horses. The potential pathogenicity of N. semolina remains to be elucidated, but the molecular technique we developed will facilitate future studies.